New Challenges in Universities: Teaching Social Entrepreneurship - Lam-Lam, Suisin; Ahumada-Tello, Eduardo; Plascencia-López, Ismael; Ovalle-Osuna, Oscar Omar; Virginia Barragán-Quintero, Reyna; Evans, Richard David; Soria-Barreto, Karla (2019 IEEE Technology Engineering Management Conference (TEMSCON), 2019)
This study analyses the importance of teaching social entrepreneurship in state universities. A survey was applied to university students to find out if personality traits are related to the characteristics of social entrepreneurship. This was achieved through Alpha Cronbach and Pearson/Spearman correlation analysis. The results show that students have the personality traits to become social entrepreneurs. However, social entrepreneurship courses are not taught in universities of Tijuana city. Therefore, it is strongly suggested to teach social entrepreneurship in universities of the city and the state because students possess social entrepreneurship traits and are interested in the subject.
Keywords: Amérique latine; Réservé UdeM; Rôle des universités

New Challenges in Universities: Teaching Social Entrepreneurship - Lam-Lam, Suisin; Ahumada-Tello, Eduardo; Plascencia-López, Ismael; Ovalle-Osuna, Oscar Omar; Virginia Barragán-Quintero, Reyna; Evans, Richard David; Soria-Barreto, Karla (2019 IEEE Technology Engineering Management Conference (TEMSCON), 2019)
This study analyses the importance of teaching social entrepreneurship in state universities. A survey was applied to university students to find out if personality traits are related to the characteristics of social entrepreneurship. This was achieved through Alpha Cronbach and Pearson/Spearman correlation analysis. The results show that students have the personality traits to become social entrepreneurs. However, social entrepreneurship courses are not taught in universities of Tijuana city. Therefore, it is strongly suggested to teach social entrepreneurship in universities of the city and the state because students possess social entrepreneurship traits and are interested in the subject.
Keywords: Amérique latine; Réservé UdeM; Rôle des universités